Effects of Dietary Phosphorus Level on the Expression of Calcium and Phosphorus Transporters in Laying Hens - Li, Peng; Wang, Rongmei; Jiao, Hongchao; Wang, Xiaojuan; Zhao, Jingpeng; Lin, Hai (Frontiers in Physiology, 2018)
The transport of calcium and phosphorus is mainly relied on their corresponding transporters. The aim of this study was to determine the effect of dietary phosphorus level on the expression of the relevant calcium and phosphorus transporters in laying hens, which has a large amount of calcium and phosphorus input from intestine and output from kidney and eggshell gland. Thirty-six 25-week-old Hy-line Brown hens were fed diets with different available phosphorus level (AP, 0.15%, 0.41%, 0.82%) respectively. The expression of phosphorus transporters type IIa and type IIb Na/Pi co-transporter (NPt2a, NPt2b), calcium transporter calbindin-D28k (CaBP-D28k), and plasma membrane Ca ATPase 1b (PMCA1b) were measured in small intestine, kidney, and eggshell gland by RT-PCR and western blot. The results showed that feed intake and serum calcitrol and PTH concentrations were not affected (P > 0.05) by dietary AP levels. Duodenum had the highest mRNA and protein expression level of NPt2b than jejunum and ileum (P < 0.05). The protein expression abundance of CaBP-D28k and PMCA1b were higher in duodenum than that in jejunum and ileum (P < 0.05). 0.15%-AP diet upregulated the ileal mRNA expression level of NPt2b and renal mRNA expression level of NPt2a (P < 0.05), while downregulated the protein abundance of NPt2b and CaBP-D28k mRNA expression in shell gland (P < 0.05). In conclusion, both the Ca and P transporters were highly expressed in duodenum. Low AP diet decreased protein expression abundance of NPt2b in duodenum while upregulated the mRNA expression level of NPt2a in kidney. The result suggests that both the phosphorus absorption in proximal intestine and its reabsorption in kidney are involved in the adaption to low AP diet.